A indisciplina na relação professor-aluno: uma análise com base na teoria dos tipos psicológicos de Jung - Ferreira, Adriana Martins (2012)
This study presents a theoretical investigation about the school indiscipline concept in the teacher-student relationship, in the basic and higher education. In order to advance the reading of that concept, explores the contributions of the proposed theory of Psychological Types by Carl Gustav Jung and the studies of indiscipline. As a research method uses a method of investigation of Conceptual Analysis, called Concept Development. The contribution of a theory of psychology to the study of school indiscipline is justified in view, which for some theorists the subject is an interdisciplinary problem, cross pedagogy, that must be studied and researched in other areas. This dialogue possibility between the themes represented an unprecedented research perspective. To develop the concept of indiscipline in the teacher-student relationship with the Psychological Types theory’s and other important studies contributions enabled us to broaden the understanding on the subject, as well as to explore other readings on the topic. The concept analysis was presented in three perspectives. First, the concept of indiscipline in the teacher-student relationship can be understood as the result either of repression or as feelings inadequacy: a personal or collective inadequacy of the feelings function, the result of centuries of repression; a teacher’s lack of skill in dealing with the student’s feelings function; an inadequate form of expression of students who have a differentiated feelings function; an exclusion of this function in the teaching-learning process, which focuses on thinking. Subsequently, the concept of indiscipline in the teacher-student relationship can be understood from the typology and the projection of those involved in this relationship: as an expression of typologicals and projections differences, generating expectations among the involved in the relationship; as expectations that end up determining or originating the students’ behaviors; as conflicts that arise among the involved because of projections related to the various psychological types; and when a particular student assumes the role of "scapegoat" due to the teacher’s or to the group’s projections. In the third perspective, the concept of indiscipline in teacher-student relationship can be understood from the contrasting features existing in extraversion and introversion attitudes: with these attitudes we may understand that the way somebody communicates and reacts to certain situations may be different according to the individual’s prevailing attitude, since each person seems to see the world or react to it in very different ways.